Thermodynamic and Kinetic Characteristics of Spinodal Decomposition in Ternary Alloys - Lopez-Hirata, Victor M.; Escamilla-Illescas, Cristobal R.; Calva-Luna, Rodrigo; Saucedo-Muñoz, Maribel L.; Avila-Davila, Erika O.; Villegas-Cardenas, Jose D. (Frontiers in Materials, 2022)
The phase decomposition of hypothetic A–B–C alloys was analyzed using the phase-field method based on the numerical solution of the Cahn–Hilliard equation. The effect of the interaction parameters on the growth kinetics of phase decomposition was also studied. The results indicated that the driving force was the fastest if all the three interaction parameters were equal, promoting the quickest growth kinetics of the ternary alloy. The phase decomposition occurred spinodally and caused the formation of three phases, A-rich, B-rich, and C-rich. In this case, the spinodal curve formed an isolated island. If one or two interaction parameters are equal to zero, the growth kinetics is slower. This condition originated only the formation of two decomposed phases with the chemical composition of either one element or two elements depending on the interaction parameters. Likewise, the spinodal curve is not completely located within the isothermal section.